Lone wolf terrorism: does it exist in Indonesia? - Chaula Rininta Anindya (2016)
On the surface, the recent individual terror attacks in Indonesia seem to be a form of lone wolf terrorism, although they are not. Yet, the relevant government agencies in counterterrorism in Indonesia are prone to cognitive bias in generalising individual attacks as lone wolf terrorism.